2016
DOI: 10.1589/jpts.28.1100
|View full text |Cite
|
Sign up to set email alerts
|

Strength and muscle activity of shoulder external rotation of subjects with and without scapular dyskinesis

Abstract: [Purpose] This study aimed to clarify the relationship between scapular dyskinesis and shoulder external rotation strength and muscle activity. [Subjects and Methods] Both shoulders of 20 healthy males were evaluated. They were classified into 19 normal, 8 subtly abnormal, and 13 obviously abnormal shoulders using the scapular dyskinesis test. Subtly abnormal shoulders were subsequently excluded from the analysis. Shoulder external rotation strength and muscle activity (infraspinatus, serratus anterior, upper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…In patients with SD, the serratus anterior muscle was less recruited. Clinically, the consequent loss of strength was appreciated by the lesser upward rotation and the greater IR of the scapula [53,54]. Stabilizer muscle fatigue seems to decrease RC strength and to increase SD symptoms [55][56][57].…”
Section: Causes and Effects Of Sdmentioning
confidence: 99%
“…In patients with SD, the serratus anterior muscle was less recruited. Clinically, the consequent loss of strength was appreciated by the lesser upward rotation and the greater IR of the scapula [53,54]. Stabilizer muscle fatigue seems to decrease RC strength and to increase SD symptoms [55][56][57].…”
Section: Causes and Effects Of Sdmentioning
confidence: 99%
“…External rotation isometric strength showed a similar trend; however, the difference was not significant ( p = 0.054). A previous study reported weakness in shoulder rotational strength with SD [ 46 , 47 ]. Judo athletes with a history of shoulder injury show reduced shoulder rotational strength [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, LSST applied in two other studies showed a very low SD prevalence [24,47]; overhead athletes accounted for 61% of the study population [48], which was much lower than in our results. Overhead athletes can exhibit SD due to repetitive overhead throwing using the scapular thoracic muscles [49,50]. Office workers experience prolonged sitting, poor work ergonomics, poor posture, repetitive work, neck and shoulder muscle fatigue, and pain [25].…”
Section: Discussionmentioning
confidence: 99%